Influence of Ambient Temperature on Fuel Consumption and Efficiency of Gas Engine in Power Plant - Ekayuliana, Arifia; Hidayati, Noor; Jovan, Arya (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
The limited production of natural gas fuel derived from fossil sources, coupled with the increasing consumption demands across various household and industrial sectors, necessitates efforts to conserve fuel usage. One of the approaches that can be taken is to enhance fuel efficiency. This study aims to analyze the influence of environmental temperature on fuel consumption and efficiency. In this research, the data used is the date or duration of the measurement, including peak load time, environmental temperature and fuel consumption. The research findings indicate that higher environmental temperatures have an inverse impact on fuel efficiency while having a linear effect on fuel consumption. For instance, at an environmental temperature of 32.8 degrees Celsius, the efficiency reaches 12.04% with a consumption rate of 0.72 KG/H, whereas at a temperature of 36.8 degrees Celsius, efficiency decreases to 8.47% with a fuel consumption of 0.96 KG/H. These findings suggest that environmental temperature can influence fuel usage efficiency, and the relationship between environmental temperature and fuel consumption is linear. This research has significant implications for optimizing fuel usage in the context of changing thermal environments.